Challenging the Tragic Mulatto Stereotype in Three Nineteen Century African American Texts - Castro-Borrego, Silvia Pilar (Cambridge Scholars, 2012)
The image of the tragic mulatta character calls for a critical exploration in the works of three literary works by 19th century African American women: Harriet Wilson's Our Nig (1859), Harriet Jacobs' Incidents in the Life of a Slave Girl (1861), and Frances W.E. Harper's Iola Leroy or Shadows Uplifted (1892). In Our Nig and Incidents the depiction of the mulatta character challenges the corrupt ethical code that justifies slavery, while Iola Leroy shows the permeation of the corrupt ethical code of the time, as it foreshadows Jim Crow (which is in full expression when Harper writes the novel) in the persistence of the corrupt code on individual, social, cultural, economic and legal dimensions.
Keywords: Afronorteamericanos; Novela estadounidense - 18..- Historia y crítica; 19th Century Racial Discurse; Harriet Jacobs; Harriet Wilson; Frances Harper; Tragic Mulatta